2008
DOI: 10.1590/s0103-84782008000100002
|View full text |Cite
|
Sign up to set email alerts
|

Persistência na água e influência de herbicidas utilizados na lavoura arrozeira sobre a comunidade zooplanctônica de Cladocera, Copepoda e Rotifera

Abstract: Em lavoura de arroz irrigado, é utilizada uma grande quantidade de agroquímicos que, dependendo da sua persistência a campo e toxicidade, podem contaminar corpos d’água e afetar organismos vivos. Com o objetivo de determinar o efeito de concentrações de campo dos herbicidas Clomazone, Quinclorac, Metsulfuron-methyl e Propanil na comunidade zooplanctônica (Cladocera, Copepoda e Rotifera), conduziu-se um experimento em viveiros de aqüicultura, de março a maio de 2005, na estação do outono. Nos dias 1°, 2°, 3°, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
0
11
1
1
Order By: Relevance
“…This may have favored an increase in the abundance obtained in the last collection, since some taxa are sensitive to low levels of dissolved oxygen. The values of hardness and alkalinity were higher than in the present study compared to data from Golombieski et al (2008) and from Reimche et al (2008). A difference in the dissociation of ions of the compounds used in the experiments could explain this disparity.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…This may have favored an increase in the abundance obtained in the last collection, since some taxa are sensitive to low levels of dissolved oxygen. The values of hardness and alkalinity were higher than in the present study compared to data from Golombieski et al (2008) and from Reimche et al (2008). A difference in the dissociation of ions of the compounds used in the experiments could explain this disparity.…”
Section: Discussioncontrasting
confidence: 95%
“…The negative influence of this pesticide was perceptible in this study, since in both collections the treated plot had the lowest abundance and diversity of taxa compared to the other treatments. This possible influence was also recorded by Reimche et al (2008), where the cladoceran assemblage showed a density variation caused by the stress of the application of this herbicide. The use of pesticides reduces the availability of food for the benthic macroinvertebrates and changes the structure of the algae community, and the toxic effect on these food resources may also be associated with this (Gagneten, 2002).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Triplicate samples were taken from each plot, comprising a 1000 mL final sample after mixing, stored into amber glass bottles and transported to laboratory. Samples were analyzed for imazethapyr according to Santos et al (2008), imazapic by Reimche et al (2008), bispyribac-sodium by Kurz (2009) and penoxsulam by Zanella et al (2003), using High Performance Liquid Chromatography with Diode Array Detection (HPLC-DAD) with a Varian system (Palo Alto, CA, USA) composed of ProStar 210 pump and ProStar 335 DAD detector. The column configuration consisted of a Phenomenex (USA) C-18 reversed-phase column (250 × 4.6 mm; 5 μm) and a Phenomenex C-18 guard column (10 × 4.6 mm; 5 μm).…”
Section: Application and Analysis Of The Test Herbicidesmentioning
confidence: 99%